Successful Therapy and Relapse Rates of Typical and Atypical Optic Neuritis: Oral Presentation - Observational Study - Ophthalmologist - M.HIDAYAT; Havilah Zeki Rosa (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : The annual incidence of Optic Neuritis (ON) has been reported increased, 0.56 and 5.1 cases per 100,000. Early diagnosis is essential to prompt an appropriate treatment, define the successfulness of therapy, and identify the incidency of relapse. The availability of neuroimaging (CT Scan, MRI) supporting diagnosis accuracy thus increase the incidence number. This paper aims at presenting the successful therapy and relapse rates of typical and atypical ON. Methods : This is an observational study towards typical and atypical ON. The sample is every patient who diagnosed with ON in the neuroophthalmology outpatient policlinic of M Djamil Hospital from January 2017 to December 2022. The sample should meet the inclusion and exclusion criteria. Every patients were treated using Optic Neuritis Treatment Trial (ONTT) protocol. The data respecting clinical characteristics, treatment results, and relapse is being collected and analyzed. Results : We collected 50 subject who meets the ON criteria, involving 69 eyes. It mostly affected women (66%), less than 50 years old (88%), unilateral (62%), and have no systemic disease (76%). The visual acuity is increased after treatment in 92.8%. 7.2% not getting better, and no visual acuity worsening. We found 2 relapse cases (4%), 1 affected the same eye, and another involve the fellow eye. Conclusion : The successful rate of therapy in typical and atypical ON is quite good. But, some patients with clinically severe ON, have systemic diseases such as diabetes, and late for treatment didn't have an improvement even after therapy. Relapse cases is found in small percentage.